Kernel Production Requirement Planning at. PT Perkebunan Nusantara V Sei Pagar - Nofirza, Nofirza (JTI: Jurnal Teknik Industri, 2018)
The production planning of palm kernel at PT. Perkebunan Nusantara V Sei Pagar not planned well yet, since the production amount frequently exceeds the demand. The sales data during 2016 shows the remaining kernel increased 2-fold amount compared to the previous year, which meaning the company experienced losses due to the decreased quality for long kept of the kernel. The purpose of this research is to prove the accuracy of production planning using exponential smoothing forecasting method so that the kernel production remains optimal. Based on data processing is obtained, the alpha value used is 0.8 with the value of MAD of 174.194.3, MSE 39599610000, MAPE of 0.4, and standard error is 219,999. The resulting test of the forecast tracking signal shows data of predicted result shows value under Â± 4 (which measn the forecast methode is feasible to use). By obtaining the calculation result using an exponential smoothing method, it is expected to be a solution for the company to reduce the overproduction.Key words: Exponential Smoothing, Forecasting, Production planning